Time-Resolved Emission Spectroscopy Measurements during the Restrike Period in Arc Plasma Torch - Alan Mašláni; Peter Ondáč; Viktor Sember; Milan Hrabovský (Journal of Spectroscopy)
Simultaneous optical, spectroscopic, and electrical measurements in the region of the arc anode attachment of the water-argon plasma torch are presented. A movement of the arc attachment along the anode surface together with its restrike mode is monitored. Temporal evolution of temperature during one cycle of the restrike mode is obtained in three different axial positions in the plasma column. Resulting temperature profiles show how the position of the arc attachment influences the plasma properties.